Zika virus differentially infects human neural progenitor cells according to their state of differentiation and dysregulates neurogenesis through the Notch pathway. Issue 1 (1st January 2019) - Ferraris, Pauline; Cochet, Marielle; Hamel, Rodolphe; Gladwyn-Ng, Ivan; Alfano, Christian; Diop, Fodé; Garcia, Déborah; Talignani, Loïc; Montero-Menei, Claudia N.; Nougairède, Antoine; Yssel, Hans; Nguyen, Laurent; et al.
ABSTRACT: Zika virus (ZIKV) is a mosquito-borne Flavivirus that causes Zika disease with particular neurological complications, including Guillain-Barré Syndrome and congenital microcephaly. Although ZIKV has been shown to directly infect human neural progenitor cells (hNPCs), thereby decreasing their viability and growth, it is as yet unknown which of the cellular pathways involved in the disruption of neurogenesis are affected following ZIKV infection. By comparing the effect of two ZIKV strains in vitro on hNPCs, the differentiation process of the latter cells was found to lead to a decreased susceptibility to infection and cell death induced by each of the ZIKV strains, which was associated with an earlier and stronger antiviral innate immune response in infected, differentiated hNPCs, as compared to undifferentiated cells. Moreover, ZIKV modulated, both in hNPCs and in vivo in fetal brain in an experimental mouse model, the expression of the Notch pathway which is involved in cellular proliferation, apoptosis and differentiation during neurogenesis. These results show that the differentiation state of hNPCs is a significant factor contributing to the outcome of ZIKV infection and furthermore suggest that ZIKV infection might initiate early activation of the Notch pathway resulting in an abnormal differentiation process, implicated in ZIKV-induced brain injury.